Barium titanate-based dielectric ceramic and preparation method thereof

By optimizing the preparation method of barium titanate-based dielectric ceramics, using multiple calcination and auxiliary agents, the problem of degradation of traditional batteries at high temperatures is solved, and high temperature stability and high energy storage density is achieved, and ceramic materials with high temperature stability and high energy storage density are extended. service life and reduce maintenance costs.

CN119263815APending Publication Date: 2025-01-07TSINGHUA UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411270711.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The performance of traditional batteries decreases after the increase in the number of charge and discharge times, the working performance drops rapidly at extreme temperatures, and the energy density is low, which limits its use in high-temperature industries and outdoor applications, and requires frequent replacement, increasing maintenance costs.

Method used

By mixing BaCO3, Bi2O3, TiO2, CaCO3, MgO, Sc2O3 and performing multiple calcination treatments, combining calcining aids and binders, the microstructure of barium titanate-based dielectric ceramics is optimized and its energy storage at high temperatures Density and energy storage efficiency.

Benefits of technology

Barium titanate-based dielectric ceramics with excellent dielectric properties and high temperature stability were prepared, which improved its energy storage density and energy storage efficiency in high temperature environments, extended service life and reduced maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263815A_ABST
    Figure CN119263815A_ABST
Patent Text Reader

Abstract

The invention discloses barium titanate-based dielectric ceramic and a preparation method thereof. The method for preparing the barium titanate-based dielectric ceramic comprises the following steps: mixing BaCO3, Bi2O3, TiO2, CaCO3, MgO and Sc2O3 to obtain a first mixture; the first mixture is subjected to first roasting treatment, a second mixture is obtained, and the roasting temperature of the first roasting treatment ranges from 800 DEG C to 900 DEG C; mixing the second mixture with a sintering aid to obtain a third mixture; mixing the third mixture with a binder, and granulating and tabletting to obtain a molded tablet; the formed sheet is subjected to rubber discharging treatment at the temperature of 500-700 DEG C so as to obtain a ceramic green body; carrying out second roasting treatment on the ceramic green body at the roasting temperature of 1000-1200 DEG C to obtain the barium titanate-based dielectric ceramic; wherein the mixed molar ratio of the BaCO3 to the Bi2O3 to the TiO2 to the CaCO3 to the MgO to the Sc2O3 is 0.8 y: 0.5 (100-y): 0.5 (100 + y): 0.2 y: 0.5 (100-y): x, 2lt; xlt; 5, 0 < y < 100. Therefore, the barium titanate-based dielectric ceramic prepared by the invention has excellent dielectric property and high-temperature stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular, to barium titanate-based dielectric ceramics and a preparation method thereof. Background Art

[0002] Although traditional battery energy storage technology is widely used in the field of modern energy storage, it also has some significant disadvantages. For example, the performance of traditional batteries will gradually decline with the increase of charge and discharge times, so the batteries need to be replaced frequently, which increases maintenance costs; the working performance of traditional batteries will decline rapidly under extreme temperature conditions, especially high temperature environments, which limits the application of traditional batteries in high-temperature industries and outdoors; the energy density of traditional batteries is low, which means that the energy they can store in the same volume is limited. Therefore, it is urgent to develop new energy storage technologies.

[0003] It should be noted that the above statements are only used to provide background technical information related to the present application and do not necessarily constitute prior art. Summary of the invention

[0004] In a first aspect of the present application, the present application provides a method for preparing a barium titanate-based dielectric ceramic, comprising: 3 、Bi 2 O 3 、TiO 2 、CaCO 3 ,MgO,Sc 2 O 3 The invention relates to a method for preparing a first mixed material and a second mixed material. The first mixed material is subjected to a first calcining treatment to obtain a second mixed material, wherein the calcining temperature of the first calcining treatment is 800°C-900°C; the second mixed material is mixed with a sintering aid to obtain a third mixed material; the third mixed material is mixed with a binder and then granulated and tableted to obtain a molded sheet; the molded sheet is subjected to a binder removal treatment to obtain a ceramic green body, wherein the binder removal treatment temperature is 500°C-700°C; the ceramic green body is subjected to a second calcining treatment to obtain the barium titanate-based dielectric ceramic, wherein the calcining temperature of the second calcining treatment is 1000°C-1200°C; wherein: BaCO 3 、Bi 2 O 3 、TiO 2 、CaCO 3 ,MgO,Sc 2 O 3 The mixing molar ratio is 0.8y:0.5(100-y):0.5(100+y):0.2y:0.5(100-y):x,2 <x<5,0<y<100。

[0005] Therefore, this application will BaCO3 、Bi 2 O 3 、TiO 2 、CaCO 3 ,MgO,Sc 2 O 3 The first mixed material obtained after mixing is used as a raw material for preparing barium titanate-based dielectric ceramics; BaCO 3 、CaCO 3 First, thermal decomposition occurs to form the corresponding metal oxide. The metal oxide generated by thermal decomposition reacts with Bi 2 O 3 、TiO 2 ,MgO,Sc 2 O 3 A solid phase reaction occurs to form a preliminary ceramic structure, and the crystal form of the ceramic structure gradually changes with the first calcination treatment to obtain a perovskite main phase; then the second mixture containing the perovskite main phase is mixed with a sintering aid to obtain a third mixture, and the sintering aid helps to reduce the sintering temperature of the material, improve the crystallization quality, and reduce the generation of defects, so that the required sintering density and strength can be achieved at a lower temperature; the third mixture is mixed with a binder and then granulated and pressed to obtain a molded sheet, and the binder will gradually decompose and volatilize during the debinding process of the molded sheet to obtain a ceramic embryo with a regular shape; the ceramic embryo removes the impurity phase during the second calcination process, so that the barium titanate-based dielectric ceramic forms a more compact and uniform microstructure. This application helps to optimize the microstructure of barium titanate-based dielectric ceramics, enhance the dielectric properties of barium titanate-based dielectric ceramics, and improve their energy storage density and energy storage efficiency in a high temperature environment by optimizing the synergistic effect between the raw materials, thereby synthesizing barium titanate-based dielectric ceramics with excellent dielectric properties and high temperature stability.

[0006] In some embodiments, the sintering aid includes MnO 2 , B 2 O 3 、SiO 2 Therefore, selecting a suitable sintering aid material is helpful to reduce the sintering temperature of the material.

[0007] In some embodiments, the mass ratio of the second mixed material to the sintering aid is 1:(0.001-0.01). Therefore, selecting a suitable mass ratio of the second mixed material to the sintering aid is helpful to reduce the sintering temperature of the material.

[0008] In some embodiments, the step of performing a first calcination treatment on the first mixed material further comprises: performing a first ball milling treatment on the first mixed material. Thus, the first ball milling treatment can make BaCO 3 、Bi 2 O3 、TiO 2 、CaCO 3 ,MgO,Sc 2 O 3 The raw material powder is crushed under the action of mechanical force, and then the crushed raw material powder is evenly mixed to form a uniform first mixed material powder. The uniform first mixed material powder helps to evenly carry out its physical and chemical changes in the subsequent first roasting treatment process, which helps to improve the sintering quality.

[0009] In some embodiments, the first ball milling treatment satisfies at least one of the following conditions: the solvent of the first ball milling treatment includes at least one of ethanol, isopropanol, and water; the ball milling speed of the first ball milling treatment is 240rpm-280rpm; the ball milling time of the first ball milling treatment is 10h-14h. Therefore, selecting a suitable solvent helps to reduce the friction between the first mixture powder particles and reduce agglomeration; selecting a suitable ball milling speed so that there is appropriate impact force and shear force between the first mixture powder and the grinding medium can both refine the first mixture powder and reduce excessive wear of the first mixture powder. Selecting a suitable ball milling time helps to fully mix and refine the first mixture powder.

[0010] In some embodiments, the aforementioned method further comprises performing a second ball milling process on the third mixed material. Thus, the second ball milling process can cause the third mixed material to be broken into third mixed material powder under the action of mechanical force.

[0011] In some embodiments, the second ball milling process satisfies at least one of the following conditions: the solvent of the second ball milling process includes at least one of ethanol, isopropanol, and water; the ball milling speed of the second ball milling process is 240rpm-280rpm; the ball milling time of the second ball milling process is 16h-20h. Thus, selecting a suitable solvent helps to reduce the friction between the third mixture powder particles and reduce agglomeration; selecting a suitable ball milling speed can refine the third mixture powder; selecting a suitable ball milling time helps to fully mix and refine the third mixture powder.

[0012] In some embodiments, the binder includes at least one of polyvinyl alcohol and polyvinyl butyral. Thus, by selecting a suitable type of binder, the plasticity and formability of the third mixed material can be improved, thereby obtaining a molded sheet with a regular shape and uniform density.

[0013] In some embodiments, the mass ratio of the third mixture to the binder is 1:(0.01-0.1). Thus, by selecting an appropriate mass ratio of the third mixture to the binder, the plasticity and formability of the third mixture can be improved, thereby obtaining a molded sheet with a regular shape and uniform density.

[0014] In some embodiments, the temperature of the first mixture is raised to the firing temperature of the first firing treatment by a first temperature-raising treatment; and / or, the temperature of the formed sheet is raised to the temperature of the debinding treatment by a second temperature-raising treatment; and / or, the temperature of the green ceramic body is raised to the firing temperature of the second firing treatment by a third temperature-raising treatment.

[0015] In some embodiments, the heating rates of the first temperature-raising treatment, the second temperature-raising treatment, and the third temperature-raising treatment are each independently 0.5 °C / min - 10 °C / min. Thus, the slow heating rate helps to reduce the thermal stress generated by the rapid temperature change of the first mixture, the formed sheet, and the green ceramic body, thereby reducing the risk of cracking of the first mixture, the formed sheet, and the green ceramic body.

[0016] In a second aspect of the present application, the present application provides a barium titanate-based dielectric ceramic prepared by the foregoing preparation method, and the barium titanate-based dielectric ceramic satisfies the chemical formula: ymol% Ba 0.8 Ca 0.2 TiO 3 -(100 - y)mol% Bi(Mg 0.5 Ti 0.5 )O 3 -xmol% Sc 2 O 3 , where 2 < x < 5 and 0 < y < 100. Thus, by controlling the molar percentages of Ba 0.8 Ca 0.2 TiO 3 , Bi(Mg 0.5 Ti 0.5 )O 3 , Sc 2 O 3 , the energy storage density and energy storage efficiency of the barium titanate-based dielectric ceramic in a high-temperature environment can be optimized, and the barium titanate-based dielectric ceramic prepared by the present application has excellent dielectric properties and high-temperature stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and / or additional aspects and advantages of the present application will become apparent and easy to understand from the description of the embodiments in conjunction with the following drawings, where:

[0018] Figure 1 is a process flow diagram of a method for preparing a barium titanate-based dielectric ceramic according to an embodiment of the present application.

[0019] Figure 2 is an X-ray diffraction pattern of the dielectric ceramics prepared in Example 1, Example 2, Comparative Example 1, and Comparative Example 2 in the present application.

[0020] Figure 3 It is a scanning electron microscope image of the dielectric ceramics prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0021] Hereinafter, the barium titanate-based dielectric ceramic and the method for preparing the same of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0022] " Scope " disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be to include end values ​​or not include end values, and can be combined arbitrarily, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 listed, and if the maximum range values ​​3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0023] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0024] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0025] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0026] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.

[0027] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0028] As a key component of high-power electronic systems, dielectric ceramics have attracted widespread attention due to their fast charging and discharging speeds and high power density. In the field of energy storage, especially in industrial applications that require stable operation in high-temperature environments, such as natural gas exploration, aerospace, and military equipment, there is a growing demand for capacitors that can maintain stable charging and discharging performance under high temperature conditions exceeding 200°C. However, achieving the dual requirements of excellent energy storage performance and maintaining temperature stability at high temperatures remains a major challenge for existing dielectric materials. Therefore, it has become particularly urgent to develop new dielectric ceramic materials to meet these requirements.

[0029] In a first aspect of the present application, the present application provides a method for preparing a barium titanate-based dielectric ceramic, referring to Figure 1 , the method comprising:

[0030] S100, BaCO 3 、Bi 2 O 3 、TiO 2 、CaCO 3 ,MgO,Sc 2 O 3 Mix to obtain a first mixture.

[0031] In some embodiments, BaCO 3 、Bi 2 O 3 、TiO 2 、CaCO 3 ,MgO,Sc 2 O3 The mixed molar ratio is 0.8y:0.5(100 - y):0.5(100 + y):0.2y:0.5(100 - y):x, where 2 < x < 5 and 0 < y < 100. Thus, BaCO 3 , Bi 2 O 3 , TiO 2 , CaCO 3 , MgO, Sc 2 O 3 After mixing, the obtained first mixture is used as the raw material for preparing barium titanate-based dielectric ceramics. By optimizing the synergistic effect among the raw materials, it helps to optimize the microstructure of the barium titanate-based dielectric ceramics, enhance the dielectric properties of the barium titanate-based dielectric ceramics, improve the energy storage density and energy storage efficiency under high-temperature environments, and thus synthesize barium titanate-based dielectric ceramics with excellent dielectric properties and high-temperature stability.

[0032] As an example, taking x = 3 and y = 50 as an example, the molar ratio of BaCO 3 , Bi 2 O 3 , TiO 2 , CaCO 3 , MgO, Sc 2 O 3 is 40:50:75:10:25:3.

[0033] S200, perform a first calcination treatment on the first mixture to obtain a second mixture.

[0034] In some embodiments, before the step of performing the first calcination treatment on the first mixture, it further includes: performing a first ball milling treatment on the first mixture. Thus, the first ball milling treatment can break BaCO 3 , Bi 2 O 3 , TiO 2 , CaCO 3 , MgO, Sc 2 O 3 into raw material powders under the action of mechanical force, and then uniformly mix the broken raw material powders to form a uniform first mixture powder. The uniform first mixture powder helps the physical and chemical changes to proceed uniformly during the subsequent first calcination treatment, which helps to improve the sintering quality.

[0035] In some embodiments, the first ball milling process satisfies at least one of the following conditions: the solvent of the first ball milling process includes at least one of ethanol, isopropanol, and water; the ball milling speed of the first ball milling process is 240rpm-280rpm; the ball milling time of the first ball milling process is 10h-14h. Therefore, selecting a suitable solvent helps to reduce the friction between the particles of the first mixture powder and reduce agglomeration; selecting a suitable ball milling speed so that there is an appropriate impact force and shear force between the first mixture powder and the grinding medium can not only refine the first mixture powder, but also reduce excessive wear of the first mixture powder. Selecting a suitable ball milling time can help the first mixture powder to be fully mixed and refined, and can also reduce the heat loss of the first mixture powder caused by long-term ball milling.

[0036] As an example, the ball milling speed of the first ball milling process may be 240 rpm, 250 rpm, 260 rpm, 270 rpm or 280 rpm.

[0037] As an example, the ball milling time of the first ball milling process may be 10 h, 11 h, 12 h, 13 h or 14 h.

[0038] As an example, the first ball milling treatment satisfies the following conditions: the solvent of the first ball milling treatment includes at least one of ethanol, isopropanol, and water; the ball milling speed of the first ball milling treatment is 240rpm-280rpm; and the ball milling time of the first ball milling treatment is 10h-14h.

[0039] In some embodiments, the first mixed material after the first ball milling process is subjected to a first drying process, thereby removing the solvent added in the first ball milling process, reducing the amount of solvent to be removed in the subsequent first calcining process, and thus improving the calcining efficiency.

[0040] In some embodiments, the drying temperature of the first drying treatment is 80° C.-120° C., and the drying time of the first drying treatment is 1 h-5 h.

[0041] As an example, the drying temperature of the first drying process may be 80°C, 90°C, 100°C, 110°C or 120°C.

[0042] As an example, the drying time of the first drying process may be 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0043] In some embodiments, the temperature of the first mixed material is raised to the calcination temperature of the first calcination process by the first temperature increase process, wherein the temperature increase rate of the first temperature increase process is 0.5°C / min-10°C / min. Thus, the slow temperature increase rate helps to reduce the thermal stress generated by the rapid temperature change of the first mixed material, thereby reducing the risk of cracking of the first mixed material.

[0044] As an example, the heating rate of the first temperature heating treatment may be 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0045] In some embodiments, the first calcination temperature is 800°C-900°C, and the first calcination time is 2h-4h. Therefore, the appropriate first calcination temperature and calcination time are selected to remove the residual solvent in the first mixed material powder and make BaCO 3 、CaCO 3 First, thermal decomposition occurs to form the corresponding metal oxide, and the carbon dioxide generated by thermal decomposition is discharged from the reaction system; then the metal oxide generated by thermal decomposition reacts with Bi 2 O 3 、TiO 2 ,MgO,Sc 2 O 3 A solid phase reaction occurs to form a preliminary ceramic structure, and the crystal form of the ceramic structure gradually changes during the first calcination process to obtain a second mixture containing a perovskite main phase.

[0046] As an example, the calcination temperature of the first calcination process may be 800°C, 820°C, 840°C, 860°C, 880°C, or 900°C.

[0047] As an example, the calcination time of the first calcination process may be 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0048] S300, mixing the second mixed material with a sintering aid to obtain a third mixed material.

[0049] In some embodiments, the sintering aid includes MnO 2 , B 2 O 3 、SiO 2 Therefore, selecting a suitable sintering aid material is helpful to reduce the sintering temperature of the material.

[0050] In some embodiments, the mass ratio of the second mixed material to the sintering aid is 1:(0.001-0.01). Therefore, selecting a suitable mass ratio of the second mixed material to the sintering aid is helpful to reduce the sintering temperature of the material.

[0051] As an example, the mass ratio of the second mixed material to the sintering aid may be 1:0.001, 1:0.002, 1:0.004, 1:0.006, 1:0.008 or 1:0.01.

[0052] In some embodiments, the method further includes performing a second ball milling process on the third mixture. Thus, the second ball milling process can break the third mixture into third mixture powder under the action of mechanical force, and the formed third mixture powder is helpful for uniform mixing with subsequent binder.

[0053] In some embodiments, the second ball milling process satisfies at least one of the following conditions: the solvent of the second ball milling process includes at least one of ethanol, isopropanol, and water; the ball milling speed of the second ball milling process is 240rpm-280rpm; the ball milling time of the second ball milling process is 16h-20h. Therefore, selecting a suitable solvent helps to reduce the friction between the particles of the third mixture powder and reduce agglomeration; selecting a suitable ball milling speed so that there is an appropriate impact force and shear force between the third mixture powder and the grinding medium can not only refine the third mixture powder, but also reduce excessive wear of the third mixture powder. Selecting a suitable ball milling time can help the third mixture powder to be fully mixed and refined, and can also reduce the heat loss of the third mixture powder caused by long-term ball milling.

[0054] As an example, the ball milling speed of the second ball milling process may be 240 rpm, 250 rpm, 260 rpm, 270 rpm or 280 rpm.

[0055] As an example, the ball milling time of the second ball milling process may be 16 h, 17 h, 18 h, 19 h or 20 h.

[0056] As an example, the second ball milling treatment satisfies the following conditions: the solvent of the second ball milling treatment includes at least one of ethanol, isopropanol, and water; the ball milling speed of the second ball milling treatment is 240rpm-280rpm; and the ball milling time of the second ball milling treatment is 16h-20h.

[0057] In some embodiments, the third mixed material after the second ball milling process is subjected to a second drying process, thereby removing the solvent added in the second ball milling process.

[0058] In some embodiments, the drying temperature of the second drying treatment is 80° C.-120° C., and the drying time of the second drying treatment is 1 h-5 h.

[0059] As an example, the drying temperature of the second drying process may be 80°C, 90°C, 100°C, 110°C or 120°C.

[0060] As an example, the drying time of the second drying process may be 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0061] S400, mixing the third mixed material with the binder, granulating and tableting to obtain a formed tablet.

[0062] In some embodiments, the binder includes at least one of polyvinyl alcohol and polyvinyl butyral. Thus, by selecting a suitable type of binder, the plasticity and formability of the third mixed material can be improved, thereby obtaining a molded sheet with a regular shape and uniform density.

[0063] In some embodiments, the mass ratio of the third mixture to the binder is 1:(0.01-0.1). Thus, by selecting an appropriate mass ratio of the third mixture to the binder, the plasticity and formability of the third mixture can be improved, thereby obtaining a molded sheet with a regular shape and uniform density.

[0064] As an example, the mass ratio of the third mixture to the binder may be 1:0.01, 1:0.02, 1:0.04, 1:0.06, 1:0.08 or 1:0.1.

[0065] S500, performing a debinding process on the formed sheet to obtain a ceramic green body.

[0066] In some embodiments, the temperature of the molded sheet is raised to the temperature of the debinding treatment by the second heating treatment, wherein the heating rate of the second heating treatment is 0.5°C / min-10°C / min. Thus, the slow heating rate helps to reduce the thermal stress generated by the rapid temperature change of the molded sheet, thereby reducing the risk of the molded sheet breaking.

[0067] As an example, the heating rate of the second temperature rising treatment may be 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0068] In some embodiments, the temperature of the debinding treatment is 500° C.-700° C., and the time of the debinding treatment is 2 h-4 h. Therefore, by selecting an appropriate temperature and time for the debinding treatment, the binder will gradually decompose and volatilize during the sintering process to obtain a ceramic green body with a regular shape.

[0069] As an example, the temperature of the debinding process may be 500°C, 550°C, 600°C, 650°C or 700°C.

[0070] As an example, the debinding treatment time may be 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0071] S600, performing a second sintering process on the ceramic green body to obtain a barium titanate-based dielectric ceramic.

[0072] In some embodiments, the temperature of the ceramic green body is raised to the firing temperature of the second firing process by the third heating process, wherein the heating rate of the third heating process is 0.5°C / min-10°C / min. Thus, the slow heating rate helps to reduce the thermal stress generated by the ceramic green body due to the rapid temperature change, thereby reducing the risk of cracking of the ceramic green body.

[0073] As an example, the heating rate of the third heating treatment may be 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0074] In some embodiments, the second calcination treatment has a calcination temperature of 1000°C-1200°C; and a calcination time of 1h-3h. In the first calcination treatment step, in addition to forming the main phase of perovskite, other impurity phases are also included. Selecting an appropriate calcination temperature and calcination time for the second calcination treatment allows the grains to continue to grow and the material to be densified, which helps to remove the impurity phases and form a more dense and uniform microstructure of the barium titanate-based dielectric ceramic, thereby improving the overall performance of the barium titanate-based dielectric ceramic.

[0075] As an example, the firing temperature of the second firing process may be 1000°C, 1050°C, 1100°C, 1150°C, or 1200°C.

[0076] As an example, the calcination time of the second calcination process may be 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0077] In summary, this application will BaCO 3 、Bi 2 O 3 、TiO 2 、CaCO 3 ,MgO,Sc 2 O 3 The first mixed material obtained after mixing is used as a raw material for preparing barium titanate-based dielectric ceramics; BaCO 3 、CaCO 3 First, thermal decomposition occurs to form the corresponding metal oxide. The metal oxide generated by thermal decomposition reacts with Bi 2 O 3 、TiO 2 ,MgO,Sc 2 O 3A solid-phase reaction occurs to form a preliminary ceramic structure. The crystal form of the ceramic structure gradually changes with the first calcination treatment to obtain a perovskite main phase. Subsequently, a second mixture containing the perovskite main phase and a sintering aid are mixed to obtain a third mixture. The sintering aid helps to reduce the sintering temperature of the material, improve the crystallization quality, and reduce the generation of defects, so that the required sintering density and strength can be achieved at a lower temperature. After the third mixture is mixed with a binder and granulated and pressed, a formed sheet is obtained. During the debinding process of the formed sheet, the binder will gradually decompose and volatilize to obtain a ceramic green body with a regular shape. Impurity phases are removed from the ceramic green body during the second calcination treatment, so that the barium titanate-based dielectric ceramic forms a denser and more uniform microstructure. By optimizing the synergistic effect between the raw materials in this application, it helps to optimize the microstructure of the barium titanate-based dielectric ceramic, enhance the dielectric properties of the barium titanate-based dielectric ceramic, and improve its energy storage density and energy storage efficiency in a high-temperature environment, thereby synthesizing a barium titanate-based dielectric ceramic with excellent dielectric properties and high-temperature stability.

[0078] In the second aspect of the present application, the present application provides a barium titanate-based dielectric ceramic prepared by the foregoing preparation method. The barium titanate-based dielectric ceramic satisfies the chemical formula: ymol% Ba 0.8 Ca 0.2 TiO 3 -(100-y)mol% Bi(Mg 0.5 Ti 0.5 )O 3 -xmol% Sc 2 O 3 , where 2 < x < 5 and 0 < y < 100. Thus, by controlling the molar percentages of Ba 0.8 Ca 0.2 TiO 3 , Bi(Mg 0.5 Ti 0.5 )O 3 , Sc 2 O 3 , the energy storage density and energy storage efficiency of the barium titanate-based dielectric ceramic in a high-temperature environment can be optimized. The barium titanate-based dielectric ceramic prepared in this application has excellent dielectric properties and high-temperature stability.

[0079] The solution of the present application is described below through specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be regarded as limiting the scope of the present application. For those not specified in the examples regarding specific technologies or conditions, they shall be carried out according to the technologies or conditions described in the literature in the field or according to the product specifications. For reagents or instruments not specified by the manufacturer, they are all conventional products that can be obtained through commercial purchase.

[0080] Example 1

[0081] S100, in this embodiment, x=3, y=50, Bi 2 O 3 5% excess, weigh 6.6423g Bi 2 O 3 4.2946 g BaCO 3 , 0.5435 gCaCO 3 , 0.5472g MgO, 3.2591g TiO 2 , 0.2293g Sc 2 O 3 into a ball mill to obtain a first mixed material; wherein BaCO 3 The purity is 99.8%, Bi 2 O 3 The purity of TiO is 99.99%. 2 The purity is 99.8%, Sc 2 O 3 The purity is 99.99%, CaCO 3 The purity of MgO is 99.99% and the purity of MgO is 99.99%.

[0082] S200. Add ethanol to a ball mill, the mass of which is twice that of the first mixture, and ball mill at a rotation speed of 260 rpm for 12 hours to obtain a slurry; pour the slurry into a watch glass, and heat the watch glass on a hot plate at 100°C for 3 hours to dry the slurry; place the dried slurry powder in a muffle furnace, and heat the muffle furnace to 850°C at a rate of 5°C / min, and keep it warm for 3 hours. After the insulation is completed, cool it with the furnace to obtain a second mixture.

[0083] S300, the second mixed material, ethanol, MnO with a purity of 99.99% 2 Add to the ball mill, MnO 2 The mass of the mixture is 0.5% of the mass of the second mixture, and the mass of the ethanol is twice the mass of the second mixture. The mixture is ball-milled at a rotation speed of 260 rpm for 18 hours to obtain a slurry. The slurry is poured into a watch glass, and the watch glass is heated on a hot plate at 100° C. for 3 hours to dry the slurry to obtain a third mixture.

[0084] S400, adding polyvinyl alcohol as a binder to the dried third mixed material for granulation and tableting to obtain a formed sheet, wherein the mass of the polyvinyl alcohol is 5% of the mass of the second mixed material.

[0085] S500, placing the formed sheet in a muffle furnace, heating the muffle furnace to 600°C at a rate of 1.5°C / min, and then keeping the temperature for 3 hours to remove the binder. After the heat preservation is completed, naturally cooling to room temperature to obtain a ceramic green body.

[0086] S600, placing the ceramic embryo in a muffle furnace, heating the muffle furnace to 1100°C at a rate of 5°C / min, and then keeping the temperature for 2 hours. After the end of the heat preservation, the ceramic embryo is naturally cooled to room temperature to obtain a barium titanate-based dielectric energy storage ceramic. The molecular formula of the barium titanate-based dielectric energy storage ceramic is (Ba 0.4 Ca 0.1 Bi 0.5 )(Mg 0.25 Ti 0.75 ) 3 -0.03Sc 2 O 3 .

[0087] The difference between Example 2 and Example 1 is that x=4.

[0088] The difference between Comparative Example 1 and Example 1 is that x=2.

[0089] The difference between Comparative Example 2 and Example 1 is that x=5.

[0090] The difference between Comparative Example 3 and Example 1 is that no MnO is added. 2 .

[0091] The dielectric ceramics prepared in Examples 1-2 and Comparative Examples 1-3 were subjected to performance tests, and the performance test items were as follows:

[0092] (1) X-ray diffraction (XRD)

[0093] The dielectric ceramics prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were subjected to XRD test. The XRD patterns are shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the dielectric ceramics prepared in Examples 1-2 and Comparative Examples 1-2 both present a single perovskite structure.

[0094] (2) Scanning electron microscopy

[0095] The dielectric ceramics obtained in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to electron microscope scanning to observe their microscopic morphology. The scanning electron microscope images are shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the grain defects of Comparative Examples 1 and 2 are more than those of Example 1, which indicates that the density of the dielectric ceramics prepared in Comparative Examples 1 and 2 is low, so their breakdown strength and energy storage density are low, and the energy storage performance is difficult to further optimize.

[0096] (3) Energy storage density U under high temperature conditions e and energy storage efficiency η

[0097] The dielectric ceramic sample prepared as above is thinned and polished to 50μm, and then a gold electrode is sputtered on the entire surface of one side, and a gold electrode with a diameter of 1mm is sputtered on the other side using a mask; then the dielectric ceramic sample is immersed in silicone oil, and the circuit is connected to test its PE curve using a ferroelectric analyzer. The PE curve test can be considered as a characteristic test that can more intuitively distinguish ferroelectrics, relaxors, and paraelectrics. At the same time, under the action of an external electric field E, the change trend of the polarization intensity P of the dielectric ceramic sample can reflect the domain inversion and energy conversion inside the material. In this embodiment, the PE curve is tested by a ferroelectric analyzer of Radiant Technologies Inc, and based on the PE curve based on the following formula:

[0098]

[0099] η=U e / (U e +U loss )

[0100] Among them, P m is the maximum polarization intensity value, Pr is the residual polarization value, E is the electric field intensity, U e is the releasable energy density, U loss is the energy density of loss, and the releasable energy storage density U is calculated by the above formulas respectively. e and energy storage efficiency η.

[0101] The energy storage density at high temperature is obtained based on the PE test curve at high temperature. During the high temperature test, the silicone oil is heated to a specified temperature using a hot plate and kept warm for more than 30 minutes before the test begins. In this embodiment, the specified temperature is 200°C.

[0102] At 200°C, the polarization intensity, energy storage efficiency η, and dielectric energy storage density U in each embodiment and each comparative example are e The results of the changes with the electric field strength are shown in Table 1, Table 2, and Table 3 respectively.

[0103] Table 1 Changes of polarization intensity with electric field strength

[0104]

[0105]

[0106] Table 2 Variation of energy storage efficiency with electric field strength

[0107]

[0108] Table 3 Variation of energy storage density with electric field strength

[0109]

[0110] As can be seen from Table 1, Table 2 and Table 3, for the barium titanate-based dielectric ceramic prepared in Example 1, when the electric field strength reaches 300 kV / cm, its polarization intensity reaches 33.51 μC / cm 2 , the energy storage efficiency reaches 88%, and the energy storage density reaches 4.2 J / cm 3 .

[0111] For the barium titanate-based dielectric ceramic prepared in Example 2, when the electric field strength reaches 275 kV / cm, its polarization intensity reaches 33.18 μC / cm 2 , the energy storage efficiency reaches 88%, and the energy storage density reaches 3.97 J / cm 3 .

[0112] In this application, the mixed molar ratio of BaCO 3 , Bi 2 O 3 , TiO 2 , CaCO 3 , MgO, Sc 2 O 3 is 0.8y:0.5(100 - y):0.5(100 + y):0.2y:0.5(100 - y):x, where 2 < x < 5 and 0 < y < 100. This also indicates that by optimizing the synergistic effect between raw materials, it helps to optimize the microstructure of the barium titanate-based dielectric ceramic, enhance the dielectric properties of the barium titanate-based dielectric ceramic, and improve its energy storage density and energy storage efficiency in a high-temperature environment. Therefore, in Comparative Example 1, x = 2, and in Comparative Example 2, x = 5, which exceeds the x range in this application, resulting in more grain defects in Comparative Example 1 and Comparative Example 2 than in Example 1. The dielectric ceramic prepared in Comparative Example 1 was broken down when the electric field strength was 275 kV / cm, and the dielectric ceramic prepared in Comparative Example 2 was broken down when the electric field strength was 225 kV / cm. Therefore, the overall performance of the prepared dielectric ceramic is lower than that of Example 1 and Example 2.

[0113] Since no sintering aid MnO 2 is added in Comparative Example 3, a dense crystal structure cannot be formed under the conditions of the first firing temperature and the second firing temperature in this application. The defects of the prepared dielectric ceramic are more than those of Example 1 and Example 2, which results in the overall performance of the dielectric ceramic prepared in Comparative Example 3 being lower than that of the dielectric ceramics prepared in Example 1 and Example 2.

[0114] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing barium titanate-based dielectric ceramics, characterized in that: include: Mixing BaCO3, Bi2O3, TiO2, CaCO3, MgO, and Sc2O3 to obtain a first mixed material; Performing a first calcination treatment on the first mixed material to obtain a second mixed material, wherein the calcination temperature of the first calcination treatment is 800° C.-900° C.; Mixing the second mixed material with a sintering aid to obtain a third mixed material; The third mixed material is mixed with a binder and then granulated and tableted to obtain a formed tablet; Performing a binder removal treatment on the molded sheet to obtain a ceramic green body, wherein the temperature of the binder removal treatment is 500° C.-700° C.; Performing a second calcination treatment on the ceramic green body to obtain the barium titanate-based dielectric ceramic, wherein the calcination temperature of the second calcination treatment is 1000° C.-1200° C.; Wherein: the mixed molar ratio of BaCO3, Bi2O3, TiO2, CaCO3, MgO and Sc2O3 is 0.8y:0.5(100-y):0.5(100+y):0.2y:0.5(100-y):x,2 <x<5,0<y<100。 2. The method according to claim 1, characterized in that The sintering aid comprises at least one of MnO2, B2O3, SiO2; and / or, The mass ratio of the second mixed material to the sintering aid is 1:(0.001-0.01).

3. The method according to claim 1, characterized in that Before the step of performing a first calcination treatment on the first mixed material, the method further includes: performing a first ball milling treatment on the first mixed material.

4. The method according to claim 3, characterized in that The first ball milling process satisfies at least one of the following conditions: The solvent of the first ball milling treatment includes at least one of ethanol, isopropanol, and water; The ball milling speed of the first ball milling treatment is 240rpm-280rpm; The ball milling time of the first ball milling treatment is 10h-14h.

5. The method according to claim 1, characterized in that The method further comprises performing a second ball milling process on the third mixed material.

6. The method according to claim 5, characterized in that The second ball milling process satisfies at least one of the following conditions: The solvent of the second ball milling treatment includes at least one of ethanol, isopropanol, and water; The ball milling speed of the second ball milling treatment is 240rpm-280rpm; The ball milling time of the second ball milling treatment is 16h-20h.

7. The method according to claim 1, characterized in that The binder comprises at least one of polyvinyl alcohol and polyvinyl butyral; and / or, The mass ratio of the third mixed material to the binder is 1:(0.01-0.1).

8. The method according to claim 1, characterized in that Performing a first temperature raising treatment to raise the temperature of the first mixed material to the calcination temperature of the first calcination treatment; and / or, Performing a second temperature increase treatment to increase the temperature of the molded sheet to the temperature of the debinding treatment; and / or, The third temperature increasing process is performed so that the temperature of the ceramic green body is increased to the firing temperature of the second firing process.

9. The method according to claim 8, characterized in that The heating rates of the first heating treatment, the second heating treatment, and the third heating treatment are independently 0.5°C / min-10°C / min.

10. A barium titanate-based dielectric ceramic prepared by the method according to any one of claims 1 to 9, characterized in that: The barium titanate-based dielectric ceramic satisfies the chemical formula: ymol%Ba 0.8 Ca 0.2 TiO3-(100-y)mol%Bi(Mg 0.5 Ti 0.5 )O3-xmol%Sc2O3, where 2 <x<5,0<y<100。

Citation Information

Patent Citations

  • Lead-free capacitor ceramics with stability at high temperature and preparation method thereof

    CN101531510A

  • Barium titanate-based dielectric ceramic with wide-temperature stable dielectric constant and preparation method thereof

    CN113603478A

  • Manufacture of barium titanate semiconductor porcelain

    JP1992196591A